Central retinal vein occlusion – A patient with systemic sclerosis - Karadžić, Jelena; Radosavljević, Aleksandra; Kovačević, Igor (Vojnosanitetski pregled, 2017)
Introduction. Scleroderma (systemic sclerosis) is a severe chronic connective tissue disease, which results in involvement of numerous internal organs. Changes in the eye are the consequences of organ-specific manifestations of scleroderma or adverse effects of immunosuppressive treatment applied. Case report. We reported a 42-year-old woman with systemic sclerosis and acute deterioration of vision in the left eye, with visual acuity 0.9. After thorough clinical examination, including fluorescein angiography and optical coherence tomography, the diagnosis of nonischemic central retinal vein occlusion was made. Further biochemical, rheumatological and immunological investigation, apart from inactive systemic sclerosis, showed normal findings. Therefore, the cause of central retinal vein occlusion could only be attributed to the microvascular changes in systemic sclerosis. After three months, visual acuity deteriorated to 0.6 due to the development of cystoid macular edema. The patient received intravitreal injection of bevacizumab and after a single dose visual acuity improved to 0.9. After a 6-month follow-up, macular edema resolved and visual acuity stabilized. Conclusion. According to our knowledge and current data from the literature, central retinal vein occlusion is a rare vision threatening manifestation of scleroderma. There are only few published case reports on central vein occlusion in scleroderma patients. Examination of the ocular fundus is recommended for evaluation of vascular disease in patients with systemic sclerosis.
Keywords: scleroderma; systemic; retinal vein occlusion; diagnosis; angiogenesis inhibitors; treatment outcome